2021
DOI: 10.1186/s12934-021-01627-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of organic carbon acquisition on growth and functional biomolecule production in diatoms

Abstract: Diatoms are unicellular photosynthetic protists which constitute one of the most successful microalgae contributing enormously to global primary productivity and nutrient cycles in marine and freshwater habitats. Though they possess the ability to biosynthesize high value compounds like eicosatetraenoic acid (EPA), fucoxanthin (Fx) and chrysolaminarin (Chrl) the major bottle neck in commercialization is their inability to attain high density growth. However, their unique potential of acquiring diverse carbon s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 82 publications
0
28
0
Order By: Relevance
“…Higher EPA yield (27 mg L −1 ) along with TAG content (92 mg L −1 ) (Figure 2A, Table 2) indicates that glycerol triggers metabolic changes resembling nitrogen depletion conditions, however, promoting growth thereby increasing the overall productivities. [ 56 ] Moreover, higher EPA content was observed on initial growth days (∼35 mg g −1 on day 6) in all mixotrophic combinations (M1, M2, M3, and M4) and was greater than previous reports showing EPA content (20, 29, 28.30, and 31.66 mg g −1 ) in mixotrophy (Supplementary Information Table S3, Figure 2A, B). [ 8,20,73 ] This indicates the necessity of structural lipids in the log phase but as nitrogen depletes in the medium EPA content did not change (Figure 2A, B) in the respective conditions, though urea‐fed cultures maintain the EPA pool throughout the experiment.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Higher EPA yield (27 mg L −1 ) along with TAG content (92 mg L −1 ) (Figure 2A, Table 2) indicates that glycerol triggers metabolic changes resembling nitrogen depletion conditions, however, promoting growth thereby increasing the overall productivities. [ 56 ] Moreover, higher EPA content was observed on initial growth days (∼35 mg g −1 on day 6) in all mixotrophic combinations (M1, M2, M3, and M4) and was greater than previous reports showing EPA content (20, 29, 28.30, and 31.66 mg g −1 ) in mixotrophy (Supplementary Information Table S3, Figure 2A, B). [ 8,20,73 ] This indicates the necessity of structural lipids in the log phase but as nitrogen depletes in the medium EPA content did not change (Figure 2A, B) in the respective conditions, though urea‐fed cultures maintain the EPA pool throughout the experiment.…”
Section: Discussionmentioning
confidence: 62%
“…An increase in EPA content in the initial growth phase was reported earlier in the presence of urea [ 32 ] and mixotrophic condition containing glycerol along with urea in P. tricornutum . [ 17,20,56 ] It was observed that in the M4 condition, EPA content was constant on day 6, 8, and 10 (Figure 2B), and the EPA titer was gradually increased throughout the experiment (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Acetyl-CoA carboxylase (ACC, B7GEB5) harboring core α-1,3-fucose residue was observed in both the wild type and PtFucT1-KO mutant. ACC is a key enzyme responsible for the catalysis of carboxylation of acetyl-CoA into malonyl-CoA in plastids [ 64 ]. However, it is still unknown which protein is responsible for the core fucose modification.…”
Section: Discussionmentioning
confidence: 99%